2018
DOI: 10.1530/eje-18-0383
|View full text |Cite
|
Sign up to set email alerts
|

DIAGNOSIS OF ENDOCRINE DISEASE: Congenital hypothyroidism: update and perspectives

Abstract: Congenital hypothyroidism (CH) may be primary, due to a defect affecting the thyroid gland itself, or central, due to impaired thyroid-stimulating hormone (TSH)-mediated stimulation of the thyroid gland as a result of hypothalamic or pituitary pathology. Primary CH is the most common neonatal endocrine disorder, traditionally subdivided into thyroid dysgenesis (TD), referring to a spectrum of thyroid developmental abnormalities, and dyshormonogenesis, where a defective molecular pathway for thyroid hormonogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
111
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 124 publications
1
111
0
8
Order By: Relevance
“…The Gruss group showed that Pax8 −/− mice developed smaller thyroid glands with absence of follicles, concluding that the aberration creates a defect in competent endoderm primordia differentiation into thyroxin‐producing follicular cells . Additionally, the disappearance of the thyroid cell precursors in Pax8 −/− mice at about E11‐11.5 suggest a putative role for PAX8 in thyroid precursor cell survival …”
Section: Animal Models Of Thyroid Dysgenesismentioning
confidence: 99%
See 4 more Smart Citations
“…The Gruss group showed that Pax8 −/− mice developed smaller thyroid glands with absence of follicles, concluding that the aberration creates a defect in competent endoderm primordia differentiation into thyroxin‐producing follicular cells . Additionally, the disappearance of the thyroid cell precursors in Pax8 −/− mice at about E11‐11.5 suggest a putative role for PAX8 in thyroid precursor cell survival …”
Section: Animal Models Of Thyroid Dysgenesismentioning
confidence: 99%
“…NKX2‐1 mutations may exhibit autosomal dominant inheritance with variable expressivity and penetrance, but frequently occur de novo . General mutational screening in three non‐syndromic TD cohorts detected no NKX2‐1 mutations …”
Section: Molecular Defects Associated To Td In Humansmentioning
confidence: 99%
See 3 more Smart Citations